2008
DOI: 10.1002/acp.1513
|View full text |Cite
|
Sign up to set email alerts
|

Questioning as an instructional method: Does it affect learning from lectures?

Abstract: What can be done to improve student engagement and learning in college lectures? One approach is to ask questions that students answer during the lecture. In two lab experiments, students received a 25-slide PowerPoint lecture in educational psychology that included four inserted multiple-choice questions (questioning group) or four corresponding statements (control group). Students in the questioning group used a personal response system (PRS), in which they responded to questions using a hand-held remote con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 36 publications
4
58
0
3
Order By: Relevance
“…Empirical evidence for the feedback principle is supported by several studies (see Moreno & Mayer, 2007; cf. also with the questioning principle postulated from Campbell and Mayer, 2009). …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Empirical evidence for the feedback principle is supported by several studies (see Moreno & Mayer, 2007; cf. also with the questioning principle postulated from Campbell and Mayer, 2009). …”
Section: Discussionmentioning
confidence: 86%
“…Students who received questions prompts in printed format or through the Internet outperformed those who received no prompts on all four dependent measures. While previous studies used learning questions in case-based learning in technology-enhanced learning environments, presented ill-structured tasks in the context of a lecture session, or used questions and feedback during a lecture (Campbell & Mayer, 2009), the present study attempts to extend these findings for computer simulations. Therefore, the third hypothesis predicts that students who are given learning questions (without feedback) about the content of the computer simulation while using the simulation perform better on retention and transfer than do students for whom these questions are absent.…”
Section: Potential Solutions To Overcome These Problemsmentioning
confidence: 87%
“…Questioning techniques have an effect size of 0.40. 6,7 Team-based learning (TBL) is popular in health science education and is a model of the flipped classroom. Studies on TBL found positive effects in student engagement, communication skills, and critical-thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…I PEK-prosjektene har man mellom annet lagt til grunn internasjonale studier som viser at spørsmålstilling i seg selv i forelesninger kan øke studenters laeringsutbytte (Roediger & Karpicke, 2006;Campbell & Mayer, 2009), men det sier seg selv at dette må forberedes nøye som en del av laeringsledelsen. Mye tyder på at slike didaktiske grep stimulerer kognitiv aktivitet og oppmerksomhet, mer enn en tradisjonell monolog fra forelesers side.…”
Section: Digitale Paradoksunclassified